2017
DOI: 10.1136/archdischild-2017-313496
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-minute consultation: A structured approach to the management of chronic cough in a child

Abstract: Coughing is a primary pulmonary defence mechanism that enhances clearance of secretions and particles from the airways and protects against aspiration of foreign materials. Coughing may affect 30% of children at any given time (1). Many are healthy children but some may have serious underlying disease. Childhood cough accounts for a large number of consultations and 80% of families who are referred to a paediatric respiratory clinic for chronic cough have sought medical advice five times or more (2). The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…If this is not the case, modern technology can be of help as parents may be asked to record their child's cough at home using smartphones or other electronic devices. 19,20 In any case, it is important to recognize the child with a chronic wet cough in due time, since this type of cough is usually associated with important underlying disorders. 21 Apart from being dry or wet, disease-specific characteristics can also be discerned; a paroxysmal cough with a classic inspiratory "whoop" points to the diagnosis of pertussis, a barking or brassy cough might be heard in tracheomalacia, whereas the occasional honking cough might fall within the "tic cough" frame.…”
Section: Sportsmentioning
confidence: 99%
See 2 more Smart Citations
“…If this is not the case, modern technology can be of help as parents may be asked to record their child's cough at home using smartphones or other electronic devices. 19,20 In any case, it is important to recognize the child with a chronic wet cough in due time, since this type of cough is usually associated with important underlying disorders. 21 Apart from being dry or wet, disease-specific characteristics can also be discerned; a paroxysmal cough with a classic inspiratory "whoop" points to the diagnosis of pertussis, a barking or brassy cough might be heard in tracheomalacia, whereas the occasional honking cough might fall within the "tic cough" frame.…”
Section: Sportsmentioning
confidence: 99%
“…21 Apart from being dry or wet, disease-specific characteristics can also be discerned; a paroxysmal cough with a classic inspiratory "whoop" points to the diagnosis of pertussis, a barking or brassy cough might be heard in tracheomalacia, whereas the occasional honking cough might fall within the "tic cough" frame. [19][20][21] Teammates: accompanying symptoms Chronic cough may be presenting as a sole symptom or as part of a clinical spectrum, which can be easily determined by asking the following "6 S" questions:…”
Section: Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that protracted bacterial bronchitis (PBB) with bacterial colonisation in lower airways is the most common reason for chronic wet cough in young children, with antibiotics for two to four weeks as the recommended treatment 4,16,17 . However, studies of children with chronic wet cough are largely based on selected patients recruited from tertiary centres 4 .…”
Section: Introductionmentioning
confidence: 99%
“…16 Studies have suggested that protracted bacterial bronchitis (PBB) with bacterial colonisation in lower airways is the most common reason for chronic wet cough in young children, with antibiotics for two to four weeks as the recommended treatment. 4,16,17 However, studies of children with chronic wet cough are largely based on selected patients recruited from tertiary centres. 4 To date, few studies have evaluated the natural course and identified risk factors for a prolonged course or an underlying chronic disease in children with recurrent episodic or chronic wet cough, including PBB.…”
mentioning
confidence: 99%